Experimental and computational analysis of binary Fe-Sn ferromagnetic compounds. (November 2019) - Fayyazi, Bahar; Skokov, Konstantin P.; Faske, Tom; Opahle, Ingo; Duerrschnabel, Michael; Helbig, Tim; Soldatov, Ivan; Rohrmann, Urban; Molina-Luna, Leopoldo; Güth, Konrad; Zhang, Hongbin; Donner, Wolfgang; et al.
Abstract: Ferromagnetic Fe3 Sn, Fe5 Sn3 and Fe3 Sn2 single crystals were synthesized using the reactive flux technique. Derived from single crystal x-ray diffraction and Transmission Electron Microscopy (TEM), a new structural model is proposed for the Fe5 Sn3 crystals - the threefold twinning of an orthorhombic unit cell with (3 + 1) dimensional space group P bcm(α00)0s0 . The spontaneous magnetization ( M s ) and the anisotropy constants K 1 and K 2 of Fe3 Sn, Fe5 Sn3 and Fe3 Sn2 single crystals were determined in a wide temperature range using M(H) dependencies and a modified Sucksmith-Thompson technique. M s and K 1 were also evaluated in the framework of Density Functional Theory (DFT) and an overall good agreement was observed between the calculated and experimental results. Furthermore, a critical evaluation of different analytical models for the assessment of magnetocrystalline anisotropy was performed, which are restricted to the analysis of uniaxial magnetic domain patterns, and it is shown that such high-throughput techniques can lead to unrealistic results. Finally, a DFT high-throughput screening of the Fe-Sn phase diagram was used to identify Fe-Sn based phases with potential to be stabilized upon alloying, and their magnetization and magnetocrystalline anisotropy were evaluated. The results show that a similar strong anisotropy as observed in Fe3 Sn may also be found in other Fe-Sn based phases, having higher potential to be used as hard magnetic material. Graphical abstract: Image 1